2021
DOI: 10.1016/j.amsu.2021.102345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative melatonin on postoperative pain following cesarean section: A randomized clinical trial

Abstract: Background Data regarding the analgesic effects of melatonin after the surgery is scare. So far, only one study has investigated the analgesic effect of melatonin during cesarean section. Objective : The present study was performed to investigate the effect of preoperative oral melatonin on pain intensity after cesarean section during spinal anesthesia. Methods In a double-blind randomized controlled clinical trial study, 204 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Melatonin provides analgesia for inflammation-associated pain in neonates and children, before venepuncture and is a safe adjunct to GA.[ 17 ] Oral melatonin 10mg administered on the night prior and 30 minutes before surgery was effective in reducing intraoperative opioid consumption under GA.[ 18 ] The same dose given before spinal anesthesia had reduced severity of postoperative pain, prolonged duration of analgesia with less need for analgesics. [ 19 ] In our study, though there was a lower intraoperative opioid consumption following melatonin premedication, the difference was not statistically significant, probably because of a lower dose of melatonin (6mg) used for premedication.…”
Section: Discussioncontrasting
confidence: 63%
“…Melatonin provides analgesia for inflammation-associated pain in neonates and children, before venepuncture and is a safe adjunct to GA.[ 17 ] Oral melatonin 10mg administered on the night prior and 30 minutes before surgery was effective in reducing intraoperative opioid consumption under GA.[ 18 ] The same dose given before spinal anesthesia had reduced severity of postoperative pain, prolonged duration of analgesia with less need for analgesics. [ 19 ] In our study, though there was a lower intraoperative opioid consumption following melatonin premedication, the difference was not statistically significant, probably because of a lower dose of melatonin (6mg) used for premedication.…”
Section: Discussioncontrasting
confidence: 63%
“…Women who delivered vaginally versus by cesarean had higher colostrum melatonin levels [ 144 , 146 ]. Finally, administering 10 mg of melatonin, compared with 5 mg or placebo, to women before the cesarean section with spinal anesthesia was shown to reduce the severity of their pain, duration of analgesic use postoperatively, and facilitated their ability to be more physically active in less time after surgery [ 147 ].…”
Section: Clinical Usesmentioning
confidence: 99%
“…A study revealed that using of 10 mg of melatonin before cesarean section significantly reduces the severity of patients' pain, increases the duration of postoperative analgesia, reduces the need for analgesics after surgery and resumption of physical activity, without any major side effects ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar discectomy is the most commonly performed surgical procedure for the treatment of patients with lumbar radiculopathy caused by for lumbosacral disc herniation ( 1 ). Despite attempts to increase the public awareness to pain assessment programs and the development of standardized pain management pathways for postoperative pain, many patients still experience severe pain following their surgery ( 1 , 2 – 3 ). Patients undergoing decompressive procedures of spine such as discectomy, could potentially experience moderate to severe postoperative pain ( 1 2 ).…”
Section: Introductionmentioning
confidence: 99%